(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s
(3ChdgG (B:s
(3GdebGdI GdChdi ef GdLRA GdKGfi ef cJGH cGed GdUfGYI GdWHjI GdHGH GdChd ai MaX GdUMI hJbSjegG hEP bO PcQfG ajeG JbOe ef bhdfG GdLRA GdChd ef cJGHfG gPG s
(3BNQgG (B:s
(3hjDNP efg ZOhI hYTjI eKbGd eY TF ef TGQH GdYSd fGaY Ef TGA Gddg JYGdi JeJ GdebGdI GdYGTQI ef GdLRA GdKGfi ef cJGH GdcGed GdUfGYI Gdedci s
(3GdLRA GdKGfi GdYedi ef fSNI SGOSIs
(3HChdgG agQS HCHhGH GdebGdGJ hjHOC HGdHGH GdChd ef GdebGd GdChdi ai MaX GdUMI hJbSjegGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
Keywords: (3GdWHs